Re Facial aesthetic injections in clinical practice: Pretreatment and post‐treatment consensus recommendations to minimise adverse outcome Region‐specific changes in line with the Covid‐19 pandemic. (10th August 2020) - Goodman, Greg J; Liew, Steven; Callan, Peter; Hart, Sarah; Somia, Naveen; Sullivan, John; Heydenrych, Izolda
Abstract: Despite the recent publication in March 2020 of guidelines for facial injectable treatments, the speed of the COVID‐19 pandemic and its safety implications necessitate changes to these guidelines The authors described what would constitute safest practice in the provision of facial injectable treatments and summarised these in table form. Adherence to a high standard of asepsis and infectious disease precautions remain a key patient safety requirement when performing facial aesthetic injections. A revision and update of these guideline summary tables follows. Changes made should enhance both patient and staff safety regarding COVID‐19/SARS‐CoV‐2, a highly infective respiratory pathogen transmitted by respiratory droplets, respiratory/mucosal secretions and contaminated fomites. Some of the additions are COVID‐19 specific and are likely to evolve and change, particularly should serological tests determining acquired immunity become available. Other additions represent further tightening of our infection control precautions.